Contribution to the parasites and associated pathology of wild Serranidae from the Aegean Sea - BAKOPOULOS, V.; NIKOLAIDIS, A.; KOLYGAS, M.; ATHANASSOPOULOU, F. (Journal of the Hellenic Veterinary Medical Society, 2018)
Parasites and associated pathology of wild caught Serranidae in the Aegean Sea were investigated in order to contribute to the scientific information regarding pathological findings of these fish. Various lesions and parasitic organisms, such as Digenean parasites, cysts and metacercaria, Cestode cysts and a nematode, were observed in the gills / pseudobranchs, liver, the wall of the digestive tract, the mesentery and the ovaries. None of these lesions were considered to be of pathogenic bacteria nature based on microscopic observation of stained tissue sections of affected organs. The most frequently observed parasitism among all the species studied was from Digenean parasites (11 out of 16 specimens examined) compared to infection by both cestodes and nematodes (3 out of 16 specimens examined). Heavier infestation was observed for the unidentified Digenean cysts that were found in the mesentery of one specimen (120 counts), followed by Didymozoan parasites (average 19.25 counts per specimen).